Gravitational Waveforms from Multiple-Orbit Simulations of Binary Neutron Stars - Lan, Nguyen Quynh; Suh, In-Saeng; Mathews, Grant J; Haywood, Reese (Communications in Physics, 2016)
<!–StartFragment–>We study the gravitational wave emission of equal-mass neutron stars in binary orbits as the stars approach the inner most last stable circular orbit. We illustrate the extraction of gravitational wave forms in a sequence of quasi-circular orbit simulations including the general relativistic hydrodynamic response of the stars. We compare the computed results with the Newtonian and post Newtonian results and show that substantial differences can arise as the orbits approach the final inspiral.<!–EndFragment–>